An innovative mechanical model for structural steel joints. (15th February 2023) - Golea, Tudor; Corman, Adrien; Mathieu, Julien; Duchêne, Yves; Jaspart, Jean-Pierre; Demonceau, Jean-François
Highlights: Mechanical modelling of structural joints is in line with Eurocode 3 and 4. An innovative mechanical model overcomes the limitations of the existing spring models. Group effects in steel plate components can be mechanically characterised. Shear force variation in the panel zone affects the response of steel joints. Implementing a mechanical model as a macro-element in FE software becomes feasible. Abstract: An innovative mechanical model for the characterisation of structural steel joints is presented in this paper. The model relies on the so-called "component method" to simulate the joints through an assembly of extensional springs and rigid elements. The proposed approach solves the inconsistencies met in the existing spring models and allows bypassing the analytical assembly procedure prescribed by the current version of Eurocode 3 for the prediction of joints' behaviour. Key features systematically disregarded in classical spring models, i.e., the group effects and the variation of shear forces on the height of the column web panel, are incorporated in the proposed mechanical model. The latter allows predicting the behaviour of steel joints respecting the European normative provisions yet based on mechanical criteria only. Comparisons with experimental and analytical results show the model's code compliance and prove its accuracy in characterising the actual behaviour of structural joints.